INTERNALIZATION OF VALUE EDUCATION IN TEMAJUK-MELANO MALAYSIA BORDER SCHOOL - Aslan, Aslan; Setiawan, Agus (Program Studi Pendidikan Agama Islam, 2019)
Social changes in human life make the challenges in the education world greater, like in Temajuk schools. This research used descriptive qualitative method. The results showed that; first, a boundary school in Temajuk was inseparable from the explorations carried out by the Paloh community in 1980; second, value internalization from schools in Temajuk does not play an important role if there is no collaboration among teachers, students and community. Third, obstacles in the education world which were caused by the effects of globalization era does not only give impact in urban areas or developing areas but also the boundary areas in Temajuk